Avaliação da atividade antitumoral do Vitanolídeo D em carcinoma de células escamosas oral: um estudo in vitro - Oliveira, Denis Francisco Gonçalves de (2025)
Cancer represents a major public health problem. Despite advances in therapies, certain types of cancer still exhibit low survival rates. Research has been focused on identifying new therapeutic targets and characterizing novel substances with antitumor activity. Among these substances, the group of phytocompounds known as withanolides has been extensively investigated. Accordingly, this study aimed to map the published information on the antitumor activity of withanolide D and also evaluated its cytotoxic activity in oral squamous cell carcinoma cell lines. A scoping review was conducted with searches in PubMed, Embase, Livivo, Scopus, Web of Science, and LILACS. The in vitro study utilized the oral squamous cell carcinoma cell line SCC-4 and the normal keratinocyte cell line HaCat. The following assays were performed: cell cytotoxicity using MTT, cell migration, cell invasion, clonogenic assay, and gene expression analysis. The results of the scoping review indicate that withanolide D has an antitumor effect primarily on leukemia, colorectal cancer, and breast cancer cell lines. Withanolide D was primarily isolated from the plant Withania somnifera and demonstrated cytotoxicity at both micro and nanomolar levels. Among the mechanisms evaluated, withanolide D acted via ceramide and modulated a crosstalk between the Akt and β-catenin pathways. In the in vitro study, it was observed that among the 7 withanolides evaluated, withanolide D had the best selectivity index with an IC-50 of 1.74 μM. This compound also reduced cell migration (p=0.0016), invasion (p<0.0001), and clonogenic capacity (p=0.0003). Notably, withanolide D appears to be involved in apoptosis induction by reducing the expression of Bcl-2 (p<0.0113). These results demonstrate that withanolide D exhibits antitumor activity in various types of cancer, including oral cancer, and may represent a promising therapeutic option for cancer treatment.